Early Detection of Bullying Victimization in Indonesian Adults: A Predictive Scoring System - Zahra Amir; Husin Sastranagara; Imanuel Simbolon; Neva Dian Permana; Andi Fatihah Syahrir (HM Publisher, 2024)
Introduction: Bullying victimization among adults is a pervasive problem with significant mental health implications, including depression, anxiety, and even suicidal ideation. Early detection of individuals at risk is crucial for timely intervention and support. This study aimed to develop and validate a predictive scoring system for bullying victimization in Indonesian adults. Methods: A cross-sectional study was conducted with 1,500 Indonesian adults aged 18-55 years. Data were collected using validated questionnaires, including the Indonesian Workplace Bullying Scale, the Kessler Psychological Distress Scale (K10), and the Rosenberg Self-Esteem Scale. Sociodemographic information and history of adverse childhood experiences were also collected. Logistic regression analysis was used to identify predictors of bullying victimization and develop a predictive scoring system. The model's performance was evaluated using receiver operating characteristic (ROC) curve analysis. Results: The prevalence of bullying victimization in the sample was 18.7%. Significant predictors included female gender, younger age, lower socioeconomic status, history of childhood trauma, low self-esteem, and high psychological distress. The predictive scoring system demonstrated good discriminatory ability, with an area under the ROC curve (AUC) of 0.82 (95% CI: 0.79-0.85). Conclusion: This study provides a validated predictive scoring system for identifying Indonesian adults at risk of bullying victimization. This tool can assist mental health professionals, employers, and policymakers in implementing targeted prevention and intervention programs to mitigate the adverse mental health consequences associated with bullying.